Treatment of Lignin Wastewater Using Peroxydisulfate Combined with Manganese Oxide-Loaded Biochar - Suwannarat, Glinsukol; Sontabam, Kemason; Sawangying, Soraya; Chaiyaraksa, Chompoonut (My University, 2022)
The pulp and paper industry wastewater discharge into public water, it will cause water pollution problems. In this research, lignin contaminated synthetic wastewater with a COD value of 2,401 mg/L, and color intensity of 5,432 ADMI was treated using 150 mM sodium peroxydisulfate in combination with MnOx-loaded biochar (MnOx-B). The MnOx-B was produced by pyrolyzing corn core at 400 °C for 4 hours without oxygen, then dipped in 40 mM manganese sulfate for 2 hours, and heated at 600°C for 30 min without oxygen. From the characterization of MnOx-B, the surface area, pore volume, pore size, and pH value at the zero-point charges of MnOx-B were 153 m2/g, 0.054 cm3/g, 1.11 nm, and 7.23, respectively. From the FTIR spectrogram, the peak assigned to Mn-O was observed. By applying 150 mM sodium peroxydisulfate and varying three parameters: MnOx-B dosage, initial wastewater pH, and reaction time, to treat lignin wastewater, the optimum experimental condition was obtained using 2 mg/L of MnOx-B, under pH of 8 for 45 min. The COD and color removal efficiencies were 73% and 90%, respectively. However, the quality of the treated wastewater did not yet pass the pulp and paper mills effluent standards of the Department of Industrial Works.
Keywords: Biochar; Lignin; Manganese oxide; Oxidation; Sodium peroxydisulfate